2012
DOI: 10.1143/jjap.51.07gc23
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Highly Sensitive Sensor Using a Surface Acoustic Wave Resonator for Wireless Strain Detection

Abstract: We developed a highly sensitive strain sensor employing a surface acoustic wave (SAW) resonator for a wireless sensing system. The aim of this study is to monitor the distribution of the strain in the earth crust or giant infrastructures, such as bridges, skyscrapers and power plants, for disaster prevention. A SAW strain sensor was fabricated using LiNbO 3 and a quartz substrate, and applied in a tensile test by attaching the steel specimen based on Japanese Industrial Standards (JIS Z2441-1). The results con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…Bao Zhongqing showed that a SAW strain sensor was fabricated using LiNbO 3 and a quartz substrate, and applied in a tensile test by attaching the steel specimen based on Japanese Industrial Standards (JIS Z2441-1). The results confirmed that the developed sensor could detect a strain of 10 −6 order with linearity [16]. Wen Wang has performed wireless measurements of SAW strain sensors using Y-cut 35 • X quartz as a piezoelectric substrate [17].…”
Section: Introductionsupporting
confidence: 62%
“…Bao Zhongqing showed that a SAW strain sensor was fabricated using LiNbO 3 and a quartz substrate, and applied in a tensile test by attaching the steel specimen based on Japanese Industrial Standards (JIS Z2441-1). The results confirmed that the developed sensor could detect a strain of 10 −6 order with linearity [16]. Wen Wang has performed wireless measurements of SAW strain sensors using Y-cut 35 • X quartz as a piezoelectric substrate [17].…”
Section: Introductionsupporting
confidence: 62%
“…The sensitivity of the devices is calculated to be Z $ 34.7 Hz m3 À1 . Although the sensitivity is not as good as those of the SAW devices made on other piezoelectric substrates, the detectable strain range is at least 5 times larger than those that have the rigidity and fragility limitation, 12,[24][25][26][27] clearly demonstrating their great potential for application in wide range strain sensing. Furthermore the sensitivity can be improved by using a thicker ZnO thin lm layer for SAW devices as demonstrated by Nalamwar et al 31 and our work on other SAW sensors and actuators.…”
Section: Strain Sensormentioning
confidence: 99%
“…Another frequently used strain sensing technology is the surface acoustic wave (SAW) [ 8 , 9 , 10 ]. SAW-based sensors monitor strain by detecting the change in acoustic wave velocity due to deformation.…”
Section: Introductionmentioning
confidence: 99%